Asynchronous Learning Method: Prospects and Challenges Among Undergraduate Students at Higher Islamic Institution in Indonesia - Kamaludin, Faisal Sundani; Ulum, Bahrul; Faizuddin, Ahmad; Azizan, Noor Azlinna (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
Distance education technologies have become viable alternatives to traditional education. While asynchronous learning allows students complete freedom of time and location, the synchronous model provides an online learning platform where instructors and students meet in the same or different locations in a virtual environment. This research aims to explore the experiences of eight undergraduate students of the Islamic Education Department at the Al Azhar University of Indonesia in the online Asynchronous Learning Method (ALM). Specifically, it investigates students’ understandings of ALM, explores their perceptions of its advantages and disadvantages, looks into their strategies in coping with challenges and obstacles they face, and their aspirations for ALM. In doing so, a qualitative case study was used to collect the data through open-ended interviews and focus group discussion (FGD) which provide personal and specific pictures of asynchronous learning. The findings revealed that apart from giving students flexibility and independence of learning, ALM has not been utilized optimally at the university level. ALM is mostly used to transfer information without the element of teaching and instructions. Hence, there is room for improvement from the current e-learning practices in which this study provides some recommendations for future online pedagogy.